Internet Banking Service quality in Malaysia: an empirical investigation - Ahmed Siddig, Mahgoub Elradi; Abdullah, Rusli; Jusoh, Yusmadi Yah; A. Jabar, Marzanah (Faculty of Electronic and Computer Engineering, Universiti Teknikal Malaysia Melaka, 2017)
This study is among the first research that develops an instrument to measure Internet Banking Service (IBS) quality in Malaysian context based on Technology Acceptance Model (TAM) and nine service quality dimensions. The objective of this research is to highlight the weaknesses and strengths of IBS quality dimensions from Malaysian users’ perspectives in order to increase the adoption of IBS. Five hundred and forty seven questionnaires were distributed and collected from the Klang Valley area in Selangor state. Data was analyzed using descriptive statistics. The study results show that Malaysian Internet Banking users’ have attitudes and intentions of using IBS (mean rating more than 3.00). Furthermore, Malaysians users realize the advantages of using IBS by giving high mean ratings for service quality dimensions to ease of use, competence, product/service portfolio, reliability, security/privacy, and relative advantage. However, other dimensions such as response and contact, efficiency, and enjoyment obtained relatively low mean ratings as indictor of users’ behavioral intentions towards IBS. Implications and suggestions for future research were given.